Benefits of implementing Industry 4.0 technology in health services - Zulkarnaen, Iskandar; Nuryono, Arif; Nugroho, Oki Widhi; Kurnia, Hibarkah; Prasmoro, Alloysius Vendhy (Universitas Sultan Ageng Tirtayasa, 2024)
The development of Industry 4.0 technology has progressed rapidly across various business sectors, including healthcare. Since the pandemic, the adoption of Industry 4.0 technologies in health services has become increasingly essential for patient care and health reporting systems. The healthcare industry demands efficiency and effectiveness, and today, numerous Industry 4.0 applications are widely utilized to streamline critical business functions in this sector. Numerous studies exploring the implementation of Industry 4.0 in healthcare can be found in academic publications. This research aims to analyze and provide a segmented review of parameters derived from a collection of articles, highlighting the extent to which Industry 4.0 technologies, or Health 4.0 (H4.0), are applied in the healthcare sector. The study employs a Systematic Literature Review (SLR) approach, drawing on research from various journals and conducting a comprehensive literature review of articles sourced from well-known databases related to Industry 4.0 in healthcare. The research identifies key Industry 4.0 technology segments based on data collected from 2019 to 2023. The findings contribute to the body of knowledge in industrial engineering, particularly in operations research and analysis, by demonstrating that the application of H4.0 is widely implemented across various segments in healthcare services. Additionally, this research offers practical insights by providing solutions for implementing Industry 4.0 technologies in healthcare, aligned with the identified segment parameters.